Capital market instruments and development in Nigeria: The mediating role of corporate taxation - Omodero, Cordelia Onyinyechi (The Economics and Finance Letters, 2026)
This research aims to evaluate the role of investment instruments in fostering capital market growth in Nigeria. It employs time series data covering the period from 1991 to 2023. The investment assets include equity, government bonds, and corporate bonds, while corporate tax is considered a moderating factor. The Vector Error Correction Model is employed for data analysis in this study. The results indicate that, in the long run, corporate bonds lead to a 6.4% increase in capital market expansion, while other predictors tend to suppress it. All things being equal, government bonds, equity, and corporate tax substantially decrease capital market growth in the long term by 4.7%, 51.4%, and 65.5%, respectively. There is a 69.1% convergence to equilibrium in the current period, meaning the previous years’ deviation from long-run asymmetry is corrected at an adjustment speed of 69.1% in the short run. A percentage change in corporate tax is associated with a 1.1% increase in capital market growth in the short term. Additionally, a percentage change in equity, government bonds, and corporate bonds in the short run decreases capital market growth by 80.9%, 10.5%, and 5.8%, respectively. Further tests show that market capitalization responds negatively to shocks from corporate bonds and equities across nearly all periods, while it reacts positively to government bonds and corporate tax. Thus, the study proposes a limit on the issuance of government bonds to foster private sector access to funds, which are essential for supporting capital market growth and performance in the country.